Realizing the Full Potential of Social Safety Nets in Africa - Beegle, Kathleen; Coudouel, Aline; Monsalve, Emma (Washington, DC: World Bank, 2018)
Poverty has been declining in Sub-Saharan Africa, but millions are still poor or vulnerable. To address this ongoing and complex problem, all countries in the region have now deployed social safety net programs as part of their core development plans. The number of programs has skyrocketed since the mid-2000s, although many interventions are still modest in size. This notable shift in social policy reflects an embrace of the role that social safety nets can play in the fight against poverty and vulnerability, and more generally in building human capital and spurring economic growth. Realizing the Full Potential of Social Safety Nets in Africa provides evidence that positive impacts on equity, resilience, and opportunity are growing, and it is clear that these programs can be good investments. For the potential of social safety nets to be realized, however, they need to expand with smart technical and design choices. Beyond technical considerations, and at least as important, this book argues that a series of decisive shifts needs to occur in three critical spheres: political, institutional, and financial: First, to recognize the role of politics in offering opportunities for expansion and in guiding design and program choice; Second, to anchor safety net programs in strong institutional arrangements that facilitate their expansion and sustainability; And third, to build sustainable financing through greater efficiency, more varied and predictable resources, and shock-responsive resources. Ignoring these spheres may lead to technically sound, but practically impossible, choices and designs. A deliberate focus on these areas is essential if social safety nets are to be brought to scale and sustained at scale. Only then will their full potential and their contribution to the fight against poverty and vulnerability be realized.